THE IMPORTANCE OF ANATOMY IN LEARNING NURSING SCIENCES - Avezova Nafisa Najmiddinovna; Askarova Dilnoz G’ulom Kizi (PEDAGOGS, 2024)
Abstract:Anatomy forms the cornerstone of medical and nursing education. It provides a detailed understanding of the human body’s structure, enabling healthcare professionals to diagnose and treat patients effectively. For nursing students, a strong foundation in anatomy is essential to comprehend the complexities of the human body and its functions, which directly influences patient care quality.